KETIDAKFASIHAN BERBICARA MAHASISWA JURUSAN SASTRA INGGRIS DALAM UJIAN SEMINAR PROPOSAL DI FAKULTAS ILMU BUDAYA (SEBUAH ANALISIS PSIKOLINGUISTIK) - WULANDARI, NILA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research is entitled ?Ketidakfasihan Berbicara Mahasiswa Saat Mengikuti Ujian Seminar Proposal di Fakultas Ilmu Budaya?. The objectives of this research are to identify the types of speech disfluencies and to analyze the causes of speech disfluencies of the students in Seminar Examinations in Faculty of Humanities, Sam Ratulangi University. The writer used descriptive method in this research. In classifying and analyzing the collected data, the writer used Fox-Tree?s (1995) theory about the types of speech disfluencies and Bortfeld?s, et al. (2001) theory about the causes of speech disfluencies. The results of this research show that silent pauses and filled pauses occurred the most because of the increase of cognitive process that results in heavy planning and delays in utterances. The speech disfluencies of the students are mainly affected by variables such as cognitive load, communication medium, topic under discussion, addressee characteristics, speaker characteristics, as well as social and situational factors. Keywords: Speech disfluencies, Psycholinguistics Analysis